Markers of bone turnover in patients with lung cancer - DANE, FAYSAL (My University, 2008)
INTRODUCTION: Bone metastases may change the primary treatment modality, especially if the bone is the only site of metastasis in patients considered to be in the early stage of lung cancer. It is usually diagnosed by imaging techniques. However, the diagnostic yields of imaging methods are limited. Some bone markers such as propeptides of type-1 collagen, pyridinoline cross-links and deoxypyridinoline (D-PYD) cross-links, serum osteocalcin, alkaline phosphatase are thought to be useful in the detection of bone metastasis in lung cancer. Thus, we aimed to determine the clinical usefulness of bone turnover markers in the assessment of bone metastases in patients with lung cancer. MATERIAL AND METHODS: Urinary D-PYD, calcium, and serum osteocalcin, calcium and total alkaline phosphatase (T-ALP) were measured in 60 lung cancer patients. Patients were evaluated by technetium 99 (99Tc) bone scintigraphy. The comparisons of measured values in patients with and without bone metastasis were done by using appropriate statistical methods. RESULTS: Fifty-four males and six females were included into study. Twenty-two patients had bone metastases, while 38 did not. Forty-two patients were nonsmall-cell lung cancer, whereas 18 were small-cell carcinoma. Urinary D-PYD level was the unique value that was statistically significantly higher in patients with bone metastases than that level in patients without bone metastasis (p < 0.05). CONCLUSION: Our study suggests that urinary measurement of D-PYD might be helpful in detecting bone metastasis in lung cancer. The high urinary D-PYD level may be an early sign of occult metastases in patients with no bone metastasis assessed by scintigraphic techniques.
Keywords: Adult; Female; Humans; Middle Aged; Biomarkers, Tumor; Aged; Male; Amino Acids; Diagnostic Imaging; Bone Neoplasms; Lung Neoplasms; Carcinoma, Non-Small-Cell Lung; Carcinoma, Small Cell